2006
DOI: 10.1111/j.1439-0450.2006.01015.x
|View full text |Cite
|
Sign up to set email alerts
|

Transboundary Animal Diseases in Pakistan

Abstract: Summary Transboundary animal diseases (TADs) are highly contagious and have the potential to spread very rapidly irrespective of the national borders, causing serious economic losses. These diseases cause high morbidity and mortality in susceptible animal populations. Furthermore, the extent of their consequences may significantly affect the food security and national economics. In Pakistan, the main TADs include rinderpest, peste des petits ruminants, foot and mouth disease and avian influenza. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…However, the recent study 'Epidemiology of PPR in Pakistan' conducted by FAO has shown that it is prevalent in all four provinces of Pakistan. Of 1463 serum samples collected, (goat 1144 and sheep 319) from 25 villages having the history of PPR outbreak, 839 goats (78.05%) and 203 (63.03%) sheep samples were found positive by cELISA (Zahur et al 2006). In Government Livestock Farms, the small ruminants are maintained in remote grazing areas where these animals may have contact with infected (wild?)…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent study 'Epidemiology of PPR in Pakistan' conducted by FAO has shown that it is prevalent in all four provinces of Pakistan. Of 1463 serum samples collected, (goat 1144 and sheep 319) from 25 villages having the history of PPR outbreak, 839 goats (78.05%) and 203 (63.03%) sheep samples were found positive by cELISA (Zahur et al 2006). In Government Livestock Farms, the small ruminants are maintained in remote grazing areas where these animals may have contact with infected (wild?)…”
Section: Discussionmentioning
confidence: 99%
“…In their presentation, Zahur et al (2006) from the Animal Health Laboratories, Animal Sciences Institute, National Agricultural Research Centre, Islamabad, reported that three serotypes of the disease, i.e. A, O and Asia 1 are prevailing in the country; serotype C was isolated only once in 1960.…”
Section: Foot and Mouth Diseasementioning
confidence: 97%
“…These data revealed that a total of 526 suspected outbreaks of PPR occurred during the period between July, 2002 and June, 2005. In these outbreaks, 8321 goats and sheep were affected out of which 4629 died with the case fatality rate of 55.63% (Zahur et al, 2006).…”
Section: Animal Transboundary Diseasesmentioning
confidence: 99%
“…Similarly the survey conducted by Khan (2010) does not mention the isolation of the causative agent of CCPP in Pakistan and the study was a more generalised survey mainly based on signs and symptoms of livestock diseases. Nothing has been mentioned regarding CCPP in the articles of Zahur et al (2006) and Afzal (2010), published in the Pakistan Veterinary Journal which has been wrongly cited in a literature review as a report on CCPP. Hussain et al (2012) isolated Mycoplasma mycoides from sick goats showing respiratory symptoms with 9.17% mortality and the respiratory disease was given the name CCPP; this does not comply with the classical definition of CCPP.…”
Section: The Term Contagious Caprine Pleuropneumonia Is Erroneously Umentioning
confidence: 99%